The Role of Single Dose Heparin in Prevention of Thrombus Formation in a New Experimental Thrombosis Model - V Nanda; R K Khazanchi; K Rakshit; P Chopra (Indian Journal of Plastic Surgery)
Vascular thrombosis continues to remain a major problem in microvascular surgery. Various antithrombotic agents have been used in experimental models in order to study their influence on the incidence of thrombosis. A new microvascular thrombosis model which utilizes a crushing artery forceps on the rat femoral vessels was used to evaluate the effect of a single does of heparin administered subcutaneously just prior to release of the crushing clamp. Patency across the traumatized segments was determined after 24 hours, by the “milking” test and by dividing the vessels downstream to the site of trauma.